2020
DOI: 10.1029/2019jd030629
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index for Asian Dust in the Ultraviolet‐Visible Region Determined From Compositional Analysis and Validated With OMI Observations

Abstract: Asian dust aerosols consist of various minerals, such as quartz, clay minerals, feldspars, and calcite. Complex refractive index of Asian dust is determined for a spectral range from 0.2 to 1.0 μm, assuming that the particles are an internal mixture of the component minerals in dust samples reported in previous literature. The derived optical constants for Asian dust are quite different from the refractive indices for other desert dusts. The imaginary refractive index for Asian dust is much smaller than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…One of the reasons for the discrepancy is the uncertainty of dust absorbability (Wang et al, 2006, 2004). The most recent study by Lee et al (2020) shows that Asian dust aerosols have smaller absorbability compared to Saharan dust, which was validated by the Ozone Monitoring Instrument (OMI) observations.…”
Section: Introductionmentioning
confidence: 79%
“…One of the reasons for the discrepancy is the uncertainty of dust absorbability (Wang et al, 2006, 2004). The most recent study by Lee et al (2020) shows that Asian dust aerosols have smaller absorbability compared to Saharan dust, which was validated by the Ozone Monitoring Instrument (OMI) observations.…”
Section: Introductionmentioning
confidence: 79%
“…Based on previous analyses on the measurements and classifications of dust mineralogy (Di Biagio et al., 2017; Kandler et al., 2007; Lee et al., 2020; Stegmann & Yang, 2017), we organized nine mineralogical groups for dust aerosols as shown in Table 1. Egan and Hilgeman (1979) found that illite has relatively lower values of the real part of the refractive index than those of the other clay minerals in the SW spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The dust CRI is primarily determined by its mineralogy (Lee et al., 2020; Moosmüller et al., 2012). Dust particles are composed of various minerals, including quartz, clay, feldspar, calcite, goethite, and hematite (Kandler et al., 2007).…”
Section: Introductionmentioning
confidence: 99%